Analisis Tingkat Perputaran Karyawan Bagian Marketing Tabungan Di PT. Bpr Indra Candra - I Gusti Made Dharma Hartawan (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
BPR Indra Candra as a business institution is inseparable from the level of competition, especially in the field of Human Resources, with a lot of competition does not rule out the possibility that the company will fail, given the development of an increasing workforce is very closely related to turnover and labor. With a good labor Recruitment analysis will be able to increase the development of the number of recruits that are able to create positive company performance. But on the data development of the number of workers in the company PT. BPR INDRA CANDRA has seen a decline every year. The purpose of this study was to analyze the level of labor turnover in the Marketing savings section at PT BPR Indra Candra. The analysis technique used is descriptive qualitative. The results showed the cause of employee turnover in the Marketing department at PT. BPR Indra Candra is an internal work environment factor, which includes first, less intense communication and secondly, the opportunity to work elsewhere.